Leptin Receptor Expression in Mouse Intracranial Perivascular Cells - Yuan, Xuefeng; Caron, Alexandre; Wu, Hua; Gautron, Laurent (Frontiers in Neuroanatomy, 2018)
Past studies have suggested that non-neuronal brain cells express the leptin receptor. However, the identity and distribution of these leptin receptor-expressing non-neuronal brain cells remain debated. This study assessed the distribution of the long form of the leptin receptor (LepRb) in non-neuronal brain cells using a reporter mouse model in which LepRb-expressing cells are permanently marked by tdTomato fluorescent protein (LepRb-CretdTomato). Double immunohistochemistry revealed that, in agreement with the literature, the vast majority of tdTomato-tagged cells across the mouse brain were neurons (i.e., based on immunoreactivity for NeuN). Non-neuronal structures also contained tdTomato-positive cells, including the choroid plexus and the perivascular space of the meninges and, to a lesser extent, the brain. Based on morphological criteria and immunohistochemistry, perivascular cells were deduced to be mainly pericytes. Notably, tdTomato-positive cells were immunoreactive for vitronectin and platelet derived growth factor receptor beta (PDGFBR). In situ hybridization studies confirmed that most tdTomato-tagged perivascular cells were enriched in leptin receptor mRNA (all isoforms). Using qPCR studies, we confirmed that the mouse meninges were enriched in Leprb and, to a greater extent, the short isoforms of the leptin receptor. Interestingly, qPCR studies further demonstrated significantly altered expression for Vtn and Pdgfrb in the meninges and hypothalamus of LepRb-deficient mice. Collectively, our data demonstrate that the only intracranial non-neuronal cells that express LepRb in the adult mouse are cells that form the blood-brain barrier, including, most notably, meningeal perivascular cells. Our data suggest that pericytic leptin signaling plays a role in the integrity of the intracranial perivascular space and, consequently, may provide a link between obesity and numerous brain diseases.